The Relationship Between Self Efficacy and High School Student Career Choices - Wulan Muliyana; Taufik Taufik (Current Issues in Counseling, 2021)
This research is motivated by the fact that there are still students who are unsure and confused about themselves in making decisions, especially on career choices. Confusion and uncertainty make it difficult for students to determine careers. This study aims to describe: (1) students' advanced career choices after graduating from high school to choose further education or work, (2) the level of self-efficacy of students who will complete high school to go to further education or work, and (3) find a relationship between self-efficacy with high school student career choices. This research uses a quantitative approach with correlational research type. The population of this study were students of class XII SMAN 14 Padang and the sample was 150 students. The instrument used was a scaled questionnaire which was analyzed using the percentage scale technique and the relationship between the two variables was analyzed using the Pearson Product Moment Correlation technique. The results showed that (1) the level of self-efficacy of students in the high category with an average percentage achievement score of 78.4%, (2) the career choice ability of students are in the high category with an average percentage score of 79%, (3) there is a significant positive relationship between self-efficacy and career choices of students with a correlation value of 0.446 at the 99% significance level. Thus it can be interpreted that the higher the student's self-efficacy, the higher the career choice ability for students and vice versa. Based on the research results, it is suggested that counselors at SMAN 14 Padang can provide assistance to students to increase self-efficacy with provide counseling guidance in the field of career guidance with material on the types of work available in the community, regarding the gradation of positions within the scope of a position, regarding the requirements for the stage and type of education, regarding the position classification system, regarding future prospects related to the real needs of society for types of features or specific job.